Клиническая оценка эффективности применения метода интраоперационной микроскопии в хирургическом лечении деструктивных форм хронического периодонтита (Эндодонтия Today)
The examination and surgical treatment of 30 patients with destructive forms of chronic periodontitis was performed. A comparative analysis of effectiveness of surgical treatment of patients with destructive forms of chronic periodontitis with the use of traditional methods and using intraoperative microscopy with the technology of retrograde filling by MTA Pro- Root. The study showed high efficiency of operation radix ectomy using intraoperative microscopy, retrograde filling by MTA ProRoot.